Asbestos Related Disorders - Raymond Bégin; André Dufresne; François Plante; Serge Massé (Canadian Respiratory Journal)
An updated summary of current understanding of asbestos related disorders is presented, along with a review of the history of the disorders, and the mineralogy, biological tissue burden, pathogenesis, pathology and clinical aspects of the asbestos related disorders, with particular emphasis on important information for the clinician.